2021
DOI: 10.1021/acs.energyfuels.0c03670
|View full text |Cite
|
Sign up to set email alerts
|

Current Status on the Manufacturing of Nanomaterials for Proton Exchange Membrane Energy Systems by Vapor-Based Processes

Abstract: Development of novel technologies for catalyst synthesis and membrane electrode assembly (MEA) fabrication is of primary importance for further improvement of the performance and economics of proton exchange membrane fuel cells (PEMFCs) and proton exchange membrane water electrolyzers (PEMWEs). While the traditional manufacturing methods are time-consuming, energy intensive, and require many processing steps, newer vapor-based methods provide many benefits including the development of improved catalysts and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…161 However, CL composites containing pyrrolic N and pyridinic N may offer superior electron and proton transfer capabilities compared to those containing graphitic N. 162 Shahgaldi et al 163 provided a comprehensive review on deposition methods for carbon-supported CLs, aiming for reduced electric resistance and enhanced stability and performance. Ouimet et al 164 observed that carbon nanotubes supporting Pt, synthesized via the chemical vapor deposition (CVD) method, exhibited relatively higher electrical conductivity compared to conventional carbon black and other synthesis methods.…”
Section: Reducing Electric Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…161 However, CL composites containing pyrrolic N and pyridinic N may offer superior electron and proton transfer capabilities compared to those containing graphitic N. 162 Shahgaldi et al 163 provided a comprehensive review on deposition methods for carbon-supported CLs, aiming for reduced electric resistance and enhanced stability and performance. Ouimet et al 164 observed that carbon nanotubes supporting Pt, synthesized via the chemical vapor deposition (CVD) method, exhibited relatively higher electrical conductivity compared to conventional carbon black and other synthesis methods.…”
Section: Reducing Electric Resistancementioning
confidence: 99%
“…Similarly, TiN coatings via heat treatment also demonstrated enhanced electronic conductivity. 183 Ouimet et al 164 discussed the coating of carbon cloth used in GDL with carbon nanotubes via the CVD method. This coating was found to be effective not only in enhancing the contact conductivity between the GDL and CL, but also in improving the conductivity between the GDL and BPP.…”
Section: Interface Micro-morphology Optimizationmentioning
confidence: 99%
“…Meierhofer and Fritsching contribute a comprehensive overview on the spray-flame synthesis of metal oxide nanoparticles, with the focus on history, processes of flame aerosol-based manufacturing, particle growth modeling, and various diagnostic techniques. Ouimet et al review vapor-based synthesis and deposition for proton exchange membrane (PEM)-based devices. The review of Rahinov et al provides comprehensive insight in the mechanism of combustion synthesis of iron oxide nanoparticles based on combined laser spectroscopy, mass spectrometry, and detailed simulation.…”
Section: Reviewmentioning
confidence: 99%
“…Low durability, to a significant extent, arises from the dissolution of Ir , with oxidation states of 3+ and 6+ . Moreover, the Ir-based catalyst for OER is characterized by mixed Ir oxidation states, depending on the preparation approach applied. , For instance, commercially available quasi-amorphous IrO x and crystalline IrO 2 are often used as the baselines . The trade-off between OER catalyst activity and stability has been established for Ir oxides.…”
Section: Introductionmentioning
confidence: 99%